The state of Malaysia : ethnicity, equity and reform - Gomez, Edmund Terence (RoutledgeCurzon Malaysian studies series, 2004)
This book provides an overview of the current state of Malaysia, looking at political developments and at governance, and discussing the impact of ethnicity, patronage and the reform movement.